Aplicaciones de los fundamentos del baloncesto como aporte al desarrollo integral en los estudiantes del octavo año de educación básica del Colegio Particular 7 de Mayo de la ciudad de Máchala, en el período lectivo 2011-2012. - Mogollón Espinoza, George Washington (2012)
This thesis is a research on the theme. Application of the fundamentals of basketball as a contribution to the comprehensive development in the Eighth Year Students of Basic Education, and consists of four chapters.